Toward a Diagnostic Score in Cushing's Syndrome - Braun, Leah T.; Riester, Anna; Oßwald-Kopp, Andrea; Fazel, Julia; Rubinstein, German; Bidlingmaier, Martin; Beuschlein, Felix; Reincke, Martin (Frontiers in Endocrinology, 2019)
Cushing’s (CS) syndrome is a classical rare disease: it is often suspected in patients who do not have the disease, at the same time, it takes a mean of 3 years to diagnose CS in affected individuals. Main reason is the extreme rarity (1-3 / million / year) in combination with the lack of a single lead symptom. CS has to be suspected when a combination of signs and symptoms is present which together make up the characteristic phenotype of cortisol excess. Unusual fat distribution in face, neck and trunk, skin changes including plethora, acne, hirsutism, livid striae and easy bruising, signs of protein catabolism such as fragile skin, osteoporotic fractures and proximal myopathy indicate the need for biochemical screening for CS. In contrast, common symptoms like hypertension, weight gain or diabetes also occur quite frequently in the general population and per se do not justify confirmatory testing. First-line biochemical screening includes urinary free cortisol excretion, dexamethasone suppression testing and late-night salivary cortisol measurements. All 3 test have overall reasonable sensitivity and specificity, and first-line testing has to be selected on the basis of the physiologic conditions of the patient, drug intake and available laboratory quality control measures. Two normal test results usually exclude the presence of CS. Other tests and laboratory parameters like the high-dose-dexamethasone-suppression test, ACTH, the CRH-test and the bilateral inferior petrosal sinus sampling are not part of the first-line-screening. To avoid unnecessary diagnostic procedures, a general rule in endocrinology should also be applied to CS: First, it needs to be evaluated if the clinical appearance is suggestive for CS. Only if the pre-test-probability for CS is high, biochemical screening should be performed. This article provides an overview about the current standard in the diagnosis of CS starting with clinical scores and screenings, the clinical signs, relevant differential diagnoses, the first-line biochemical screening and ending with a few exceptional cases.